Experimental study on interfacial shear behavior of PBL shear connector deeply embedded in UHPC - Zhipeng Cao; Zhengwei Li; Shaowei Deng; Lei Wang; Haibo Jiang; Bingxiong Xian (Case Studies in Construction Materials, 2023)
To analyze the shear capacity and failure mechanism of perfobond strip (PBL) connectors in the junction of the steel-UHPC composite pedestrian truss bridge, this study conducted monotonic loading push-out tests on four specimens of PBL shear connector deeply embedded in UHPC and one specimen in normal concrete. The research primarily investigated the interfacial shear behavior of PBL connectors under static load, focusing on the effects of different concrete types, embedded depth of PBL connector, and diameter of transverse reinforcing bar, especially in the situation with a deep 240 mm embedded depth of PBL connectors. The results showed that the shear capacity of PBL connector in UHPC was 76% higher than that in normal concrete specimen. For UHPC specimens with 240 mm embedded depth, the failure mode of the specimens with 16 mm and 25 mm transverse reinforcing bar diameter was steel plate destroy while the specimens with 12 mm transverse reinforcing bar diameter showed transverse reinforcing bar fracture. Reducing the embedded depth of the PBL connector with 12 mm diameter transverse reinforcing bar increased the initial stiffness and shear capacity of PBL connector, but decreased the ductility. In this study, the experimental results were compared with several calculation equations, and a modified equation was proposed for PBL connectors deeply embedded in UHPC based on the force transferring mechanism and different failure modes. The predicted results were in good agreement with the experimental results. Furthermore, some design suggestions for PBL connectors deeply embedded in UHPC were concluded in this paper.